The challenges of the competitive development of the Brazilian Oil and Gas sector in the context of pre-salt - Part III - Azevedo Filho, E. T.; Palma, M. A. M.; Perestrelo, M.; Lira, R. A. (Boletim Petróleo, Royalties e Região, 2016)
This work is the third and last in a series of three articles, wich purpose was to analyse the challenges of the competitive development of the Brazilian O&G sector. The main elements involved, as well as the dynamics that comprise the context of the competitive development of the national suplier companies located in the O&G cluster in ther Campos Basin, were identified, in this Part III, from the use of the Strategic analysis of actors. Considering the results found, it was concluded that it is possible to achieve a higher qualification in the forms of participation of the actors in the process of intervention and change in cases as the one illustrated in this work.